Why marriages succeed or fail : and how you can make yours last - Gottman, John (New York : Fireside book, 1994)
Contenido: What makes marriage work? Marriage styles: the good, the bad, and the volatile. The four horsemen of the apocalypse: warning signs. Your Private thoughts become cast in stone. The two marriages: his and hers. Your marriage: the diagnosis. The four keys to improving your marriage. Strengthening the foundations.